A chameleon AIEgen exhibiting six distinct yet tunable thermal and photoswitchable states - Xinyuan He; Baochuan Hu; Xin Wang; Xing Feng; Xinyuan Wang; Xinmeng Chen; Jianwei Sun; Jacky W. Y. Lam; Lianrui Hu; Ben Zhong Tang (Nature Communications)
Abstract Seeking methods to realize multiple fluorescence changes in a single luminogenic system is of great importance for both chemistry and bionics research. Due to the lack of effective strategies and functional motifs, luminogens with multiple switching and controllable models are still scarce. Herein, we report a chromone-based aggregation-induced emission luminogen called Z-CDPM, which exhibit six distinct, tunable thermal and photoswitchable states, offering controllable thermochromic or photochromic behavior under varying conditions. Specifically, five different reactions are involved: reversible Z/E isomerization, irreversible cyclization and elimination under thermal treatment, and photoarrangement of Z-CDPM and its thermal cyclization product under UV irradiation. The relative independence of the switching states is effectively maintained. Experimental and theoretical analyses validate our design strategies and provide valuable insights into the detailed mechanisms of these reactions, and single crystals further confirm their structures. Additionally, practical applications, including multiple-colored images, quick response codes, and an advanced information encryption system, are developed to demonstrate the utility. This work thus provides effective strategies and structural motifs for the design of multiresponsive luminogens and multifunctional systems.